2016
DOI: 10.1038/srep30194
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Ce Valence in RE2Fe14B Tetragonal Compounds by La-Ce Co-doping: Resultant Crystallographic and Magnetic Anomaly

Abstract: Abundant and low-cost Ce has attracted considerable interest as a prospective alternative for those critically relied Nd/Pr/Dy/Tb in the 2:14:1-type permanent magnets. The (Nd, Ce)2Fe14B compound with inferior intrinsic magnetic properties to Nd2Fe14B, however, cannot provide an equivalent magnetic performance. Since Ce valence is sensitive to local steric environment, manipulating it towards the favorable trivalent state provides a way to enhance the magnetic properties. Here we report that such a desirable C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 31 publications
0
34
1
Order By: Relevance
“…This indicates that for our film, not only the magnetic moment but T C is also higher than bulk. In order to further confirm if T C of the film is indeed higher than the bulk in the T S =750°C film, we measured magnetization of this film and that of bulk as a function of temperature (M-T) in an applied field of 1 kOe [30]. Figure 5(b) shows the dM/dT versus T curves of these materials.…”
Section: Discussionmentioning
confidence: 93%
“…This indicates that for our film, not only the magnetic moment but T C is also higher than bulk. In order to further confirm if T C of the film is indeed higher than the bulk in the T S =750°C film, we measured magnetization of this film and that of bulk as a function of temperature (M-T) in an applied field of 1 kOe [30]. Figure 5(b) shows the dM/dT versus T curves of these materials.…”
Section: Discussionmentioning
confidence: 93%
“…In this work, we successfully prepared the high-performance Nd-Ce-Fe-B film with a high Ce concentration of more than 50 wt.% Ce substitution. Although important progresses have been made 6 9 , 11 , 13 15 , the magnetic properties of Ce magnets with a Ce-substitution proportion higher than 50 wt.% are still low. The magnetic properties achieved in our film (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This magnet shows a good cost-performance in comparison with a 48.9 MGOe La/Ce-free commercial magnet 14 . It is also found that the La-Ce doping conduces to the magnetically favorable Ce 3+ state 15 . For 50 wt.% La, Ce and La-Ce substitution (La/Ce ratio is 1.86), sintered magnets achieve the coercivity of 0.8 kOe, 5.7 kOe and 6.6 kOe, respectively 15 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…reported a mixed-valent state with the coexistence of Ce 3+ and Ce 4+ atoms in the Ce 2 Fe 14 B phase based on the evidence provided by Ce L 3 -edge x-ray absorption near-edge structure measurement 13 . Their steric variation combined with different electron density give rise to the valence state dependent magnetic and metallurgical behaviors of Ce-Nd-Fe-B alloys 14,15 . The last but not the least, an abnormal increase of coercivity has been observed in the Ce-Nd-Fe-B alloys with around 25% Ce-substitution, and several researchers have attributed it to the phase separation 2,1618 .…”
Section: Introductionmentioning
confidence: 99%